Kebijakan Hukum Pemerintah Dalam Mengatasi Plastik Sekali Pakai Dan Dampaknya Terhadap Lingkungan - Muhammad Fahrudin; Irwan Triadi (Jurnal Relasi Publik, 2024)
The issue of plastic bags continues to be a significant topic globally in waste management. Their relatively low cost, ease of use, and accessibility have made plastic bags an integral part of human life. With increasing plastic bag usage, inevitably comes an increase in plastic waste. Moreover, the rapid usage cycle of plastic bags, as they are typically single-use items used only temporarily, exacerbates the problem. If plastic waste is not optimally managed, it will have negative environmental impacts. To address this, the retail company Alfamart has begun employing green marketing strategies to promote the "Plastic Bag Diet" by offering environmentally friendly shopping bag products (Eco Bags). This aims to raise awareness and concern among the public for environmental sustainability by reducing plastic bag usage during shopping. Apart from Alfamart, other competing retail companies have also adopted similar strategies and offer eco-friendly bag products. The intensifying competition among retail companies forces managers to reconsider their strategies to win market share. The issuance of the Bali Provincial Regulation on Limiting Single-Use Plastic Waste is based on Article 12 paragraph (3) and Article 13 paragraph (2) of Bali Provincial Regulation Number 5 Year 2011 concerning Waste Management. This reflects the negative impacts that can arise if waste is not properly managed. The enactment of local regulations prohibiting the use of single-use plastic indicates a legal policy direction towards environmental conservation. The research method used in this study is a juridical normative method with a literature review approach, focusing on legal norms including principles, norms, rules, regulations, agreements, and doctrines. Therefore, this study aims to analyze the effects of green marketing on attracting purchasing interest and persuading the public to make purchasing decisions on Eco Bag products at Alfamart as alternatives to plastic bags.